Energy, economic and environmental analysis and comparison of the novel Oxy- combustion power systems - Ozsari, Ibrahim; Ust, Yasin (Yildiz Technical Univ, 2022)
Oxy-combustion technologies are clean energy systems with zero emission; they have great potential when considering global warming and climate change. This study presents a detailed thermodynamic analysis in terms of energy, environment, and economy. Consequently, the results obtained for an oxy-combustion power system are presented in comparison with a conventional gas turbine power system. The results are presented as a function of the pressure ratio with regard to net power, input heat, system efficiency, specific fuel consumption, equivalence ratio, fuel-air ratio, capital investment cost, fuel cost, oxygen cost, total cost, electricity revenue, and net profit. In addition, the study calculates the pollutant emissions from non-oxy-combustion systems and investigates the environmental costs. The pressure ratio for maximum net power has been obtained as 20.8 in the conventional gas turbine power system. Similarly, the pressure ratios for maximum net power in oxy-combustion power cycles with 26%, 28%, and 30% oxygen ratios are 23.3, 27.4 and 29.7, respectively. Results from 24% to 30% have been displayed to observe the effect of reactant oxygen in the oxy-combustion power cycles. The optimum cycle conditions have been determined by calculating the costs of system components, total revenues, and net profits at pressure ratios of 10, 20, 30 and 40. Finally, the results reveal the pressure ratio should be reduced to minimize the total costs per cycle. For maximum net profit, the pressure ratio in a conventional gas turbine power cycle has been calculated as 15.9; similarly, the pressure ratios in oxy-combustion power cycles with 26%, 28%, and 30% oxygen ratios have been respectively calculated as 12.8, 15.2 and 16.4.
Keywords: Thermodynamic Analysis; Oxy-combustion Cycle; Gas Turbine; Clean Energy; Thermal Efficiency; Oxy-fuel/s-CO2 Cycles